KONTRIBUSI GAYA KEPEMIMPINAN KEPALA SEKOLAH BERBASIS CATUR NAYA SANDHI TERHADAP KINERJA GURU PADA SMA NEGERI 2 SINGARAJA - Sukadi Sukadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study was aimed at explaining the contribution of the headmaster leadership style on the basis of Catur Naya Sandhi toward the teachers’ work performance of SMA Negeri 2 Singaraja. To achieve the objective this study was conducted by expost facto survey with multiple correlation study between four independent variables of headmaster leadership style (sama, beda, dana, danda) and one dependent variable, namely teacher’s work performance. This research was conducted to all teachers of SMA Negeri 2 Singaraja. All 54 teachers were involved as samples in this study. Data in this survey were collected by distributing the questionnaires of headmaster leadership style (sama, beda, dana, danda) and teachers’ work performance. All data in this study were numerical data with interval scale and then were analyzed by multiple and partial regression. The result of this research showed that there were significant contributions of four headmaster leadership styles on the basis of Catur Naya Sandhi toward teachers’ work performance of SMA Negeri 2 Singaraja both simultaneously and partially. The implication of this study is that school headmasters need to more improve the quality of their four leadership styles implementation on the basis of Catur Naya Sandhi to enhance the quality of teachers’ work performance.